Pemilihan Lokasi Ideal pada Bank Syariah Indonesia Strategi dan Pertimbangan Utama - Putri, Asa (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2024)
Bank Syariah Indonesia (BSI) plays an important role in expanding sharia financial inclusion in Indonesia, especially amidst intense competition in the banking industry. Choosing the ideal location for a bank office is a strategic decision that influences accessibility, customer satisfaction and operational performance. A strategic location not only considers demographic aspects, such as Muslim population density, but also economic potential, infrastructure and the level of competition in the region. Therefore, this research aims to analyze the main strategies and considerations in selecting the ideal BSI office location to support operational efficiency and business growth. This research uses a qualitative approach with descriptive analysis methods. The data used is secondary data, including BSI annual reports, Financial Services Authority (OJK) publications and related literature studies. The research results show that BSI's strategic location selection was influenced by several main factors, such as high Muslim population density, adequate infrastructure, and regional economic potential. In addition, the integration of technology in office layout design, such as digital services and electronic queuing systems, also improves customer experience and operational efficiency. These findings provide important insights for developing optimal location strategies to support the growth of sharia banking in Indonesia